Eksplorasi Penggunaan dan Manfaat Handphone dalam Pembelajaran Matematika pada Kurikulum Merdeka SMPN 29 Medan - Mawaddah, Fiha (MODELING: Jurnal Program Studi PGMI, 2025)
This study aims to explore the perceptions of students and educators as well as the form of cellphone use in learning mathematics in the Merdeka Curriculum at SMPN 29 Medan. This research uses a descriptive qualitative approach with data collection techniques in the form of observation, interviews, and documentation. The research subjects consisted of five students in class VIII-6 and one mathematics educator. The results showed that the majority of students and educators had a positive perception of the use of cellphones as learning aids. Mobile phones are considered capable of improving concept understanding, especially in congruent materials, through the use of applications such as GeoGebra and learning videos. In addition, students also use mobile phones to access Google Forms, search for additional information, and learn independently according to the principle of differentiation in the Merdeka Curriculum. However, there are also some obstacles such as concentration disorders due to uncontrolled use. Therefore, the role of educators is very important in providing direction and supervision so that cellphone utilization remains focused on learning objectives. These findings reinforce the importance of wise and purposeful integration of digital technology in mathematics learning in the Independent Curriculum era. Abstrak Penelitian ini bertujuan untuk mengeksplorasi persepsi peserta didik dan pendidik serta bentuk penggunaan handphone dalam pembelajaran matematika pada Kurikulum Merdeka di SMPN 29 Medan. Penelitian ini menggunakan pendekatan kualitatif deskriptif dengan teknik pengumpulan data berupa observasi, wawancara, dan dokumentasi. Subjek penelitian terdiri dari lima peserta didik kelas VIII-6 dan satu orang pendidik matematika. Hasil penelitian menunjukkan bahwa mayoritas peserta didik dan pendidik memiliki persepsi positif terhadap penggunaan handphone sebagai alat bantu pembelajaran. Handphone dianggap mampu meningkatkan pemahaman konsep, terutama dalam materi kongruen, melalui penggunaan aplikasi seperti GeoGebra dan video pembelajaran. Selain itu, peserta didik juga memanfaatkan handphone untuk mengakses Google Form, mencari informasi tambahan, dan belajar secara mandiri sesuai prinsip diferensiasi dalam Kurikulum Merdeka. Namun, ditemukan pula beberapa kendala seperti gangguan konsentrasi akibat penggunaan yang tidak terkontrol. Oleh karena itu, peran pendidik sangat penting dalam memberikan arahan dan pengawasan agar pemanfaatan handphone tetap terfokus pada tujuan pembelajaran. Temuan ini memperkuat pentingnya integrasi teknologi digital secara bijak dan terarah dalam pembelajaran matematika di era Kurikulum Merdeka.